METHODS FOR MEMORIZING THE QUR'AN AT TAHFIZH Islamic BoardingSchool - Ahyar Rasyidi (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to describe the method of memorizing the Al-Qur'an at the TahfizhAl-Qur'an Islamic Boarding School in South Kalimantan. The Tahfizh Al-Qur'an Islamicboarding school has increasingly existed and attracted the attention of the public sinceit became a formal institution in Indonesia under the Ministry of Religion, in addition toseveral non-formal Tahfizh Al-Qur'an Islamic boarding schools which carry out learningindependently but remain committed to producing memorize the Koran. This researchuses a qualitative method with a narrative descriptive approach, where the data sourceis taken from the results of field research. As well as secondary data taken fromresearch results that have been published in journals. The data analysis technique usedis data reduction which concludes the results of related research. The results of theresearch stated that of the three Al-Qur'an tahfizh Islamic boarding schools studied,there were several methods used.Of the three Al-Qur'an tahfizh Islamic boardingschools studied, there were several methods used, including the Tikrar method,Talqin method, Yanbu'a method, Halaqoh method and Talaqqi method.Therefore, themethod of memorizing the Al-Qur'an in Al-Qur'an Tahfizh Islamic boarding schools inSouth Kalimantan can be said to be not uniform. Some of the methods used in TahfizhIslamic boarding schools often circulate within the framework of teacher-student orinter-institutional relations, as is the model of knowledge transmission in Islamicboarding schools in general. On the other hand, there are Islamic boarding schools thatdevelop memorization methods that are adapted to the conditions of the students,caregivers or boarding school managers who develop memorization methods, to makethings easier for the students.Education Studies an